Special Issue on “Buildings and Structures under Extreme Loads II” - Chiara Bedon; Flavio Stochino; Daniel Honfi (Applied Sciences, 2022)
Exceptional loads on buildings and structures are known to take origin and manifest from different causes, like natural hazards and possible high-strain dynamic effects, human-made attacks and impact issues for load-bearing components, possible accidents, and even unfavorable/extreme operational conditions [...]